Esterification of high free fatty acid jatropha curcas oil for biodiesel production = أسترة زيت الجاتروفا كركاس علي الأحماضي الدهنية الحرة لإنتاج الوقود الحيوي - Abdelrahman, Maha A. A; Ahmad Yassin, Atif Abdul Mun'im; Hussein, Ismail Hassan; Mirghani, Mohamed Elwathig Saeed; Abdullah, Babiker Karamah (Deanship of Scientific Research, University of Gezira, 2018)
The study investigated the esterification of high free fatty acid (FFA) Jatropha curcus (J. curcus) seed oil (6.3 - 14.6%) to produce biodiesel using sulfuric acid with reaction parameters 1% H2SO4, 600 rpm at 60oC and one hour reaction time. At methanol to oil ratio 3:1, FFA were reduced to 4.73% with conversion 45%; at 6:1 methanol to oil ratio, FFA were reduced to 2.31% with conversion 72%; at 7.5:1 methanol to oil ration FFA were reduced to 2% with conversion > 85%and there is no considerable difference when increasing methanol to oil ratio to 9:1. Hence, the optimum methanol to oil ratio is 7.5:1, moreover, the esterification process is not affected by the initial FFA%.